Nutrition and weather effects on population dynamics of insect-pests in potato (Solanum tuberosum) - KUMAR, VIVEK; AULAKH, C S; KOONER, RUBALJOT; KAUR, JASHANJOT (The Indian Journal of Agricultural Sciences, 2021)
Insect population studies were conducted to estimate the relative population abundance of sucking insect-pests on potato (Solanum tuberosum L.) in relation to nutrition management and weather parameters at Punjab Agricultural University, Ludhiana, India during rabi 2014-15 and 2015-16. The lowest and the highest aphid, jassid and whitefly populations were recorded with recommended dose of manures and fertilizers (T1-RDMF), and the unfertilized control (T10), respectively during 46th to 51st Standard Meteorological Week (SMW). Seasonal fluctuation of insectpest- infestation revealed that the weather parameters influenced the insects population. The aphid population was the lowest (0.27/plant) during 46th SMW and it increased with advancement in the crop growth stage with its highest population (3.43/plant) during 52nd SMW. Contrary to the aphid population, the highest populations of jassid (2.89/ plant) and whitefly (2.23/plant), irrespective of the nutrition treatments, were recorded during 47th SMW, and decreased with advancement of the crop-growth stage with the lowest population (0.49 jassid and 0.55 whitefly/plant) being during 52nd SMW. A negative correlation was observed between the aphid population, and the maximum-(Tmax) and minimum-temperatures (Tmin) and sunshine hours (SH) but the positive correlation with relative humidity (RH). However, the trends for the jassid and whitefly populations were the opposite.